Smart casual : towards excellence in sessional teaching in law : final report 2018. - Heath, Mary; Hewitt, Anne; Galloway, Kate; Israel, Mark; Skead, Natalie; Steel, Alex (Australia. Dept of Education and Training (DET), 2018)
The Smart Casual project was designed to create and disseminate resources to address a demonstrated national need for discipline-specific professional development for sessional law teachers. Sessional staff deliver half of Australian tertiary teaching. The quality of that teaching is crucial to student learning, retention and progress. Yet national research, as well as a needs analysis conducted as part of the Smart Casual seed project, suggests that support and training for sessional teachers remain inadequate. aw schools across Australia vary widely in size and resources, use of online and blended learning, rural and urban settings, the nature of their programs, and student demographics. To ensure the program met the needs of sessional staff across these diverse contexts, a project team was established with members from diverse institutional types and settings. Smart Casual recruited an expert review group comprising leading Australian and international legal educators with knowledge of a range of institutional settings. [Executive summary, ed]